GW24-e3508 Effects of coronary effluent from ischaemic postconditioned rat hearts on in vitro proliferation and survival of mesenchymal stem cells under hypoxia. (1st October 2013) - Jun, Fang; Fan, Lin; Lianglong, Chen; Xiangqi, Chen; Lingzhen, Wu
Abstract : Objectives: Mesenchymal stem cells are sensitive to hypoxia under myocardial micro-environment of ischaemia and reperfusion. Ischemic postconditioning, which is cardioprotective against ischaemia-reperfusion injury, enhances in vivo survival and therapeutic effects of transplanted stem cells. In this study, we investigateded the effects of coronary effluent from postconditioned rat hearts on proliferation and survival of mesenchymal stem cells in vitro under hypoxia. Methods: Isolated perfused rat hearts were subjected to 30 minutes of ischaemia and 60 minutes of reperfusion, and postconditioning was induced by 3 cycles of 30 sec reperfusion and 30 sec ischaemia before sustain edreperfusion. Inflammation-related factors in coronary effluent were assessed by ELISA. Mesenchymal stem cells from bone marrow of Sprague-Dawley rats were cultured with coronary effluentunder hypoxia (95% nitrogen and 5% carbon dioxide)for 18 hours. Cell proliferation was determined by methylthiazolyl tetrazolium. Survival was detected by Annexin V/PI. Results: Compared with ischaemia-reperfusion group, postconditioning treatment increased the level of interleukin-10 and decreased the level of tumour necrosis factor-α, interleukin-1β in coronary effluent ( P < 0.01). Stem cells with postcondition edeffluent culture had a higher proliferation (optical density value), more surviving cells and less necrosis ccompared with ischaemia-reperfusion effluent ( P < 0.01). Conclusions: We have demonstrated that coronary effluent from postconditioned hearts may promote the proliferation and survival of mesenchymal stem cells by suppressing inflammation under hypoxia.